Successful Removal of a Biliary Stent in the Jejunum Using Double-Balloon Enteroscopy: - Saeedi, Sandra; Dooghaie Moghadam, Arash; Razavi-Khorasani, Niloofar; Eslami, Pegah; Farokhi, Ermia; Moazzami, Bobak; Mehrvar, Azim; Iravani, Shahrokh; Reza Hashemi, Mahmood; Dooghaie Moghadam, Masoud (Galen Medical Journal, 2020)
Background: Plastic biliary stent placement has been widely used as a safe approach for the management of hilar neoplasms or the dilation of benign biliary obstruction. Despite the complexity of this procedure, this approach is followed by a few complications. The incidence rate of stent migration is about 10%. In a majority of cases, the migrated stents are retained within the gastrointestinal tract and pass through the intestine with no complication or need for medical intervention. Case Report: In this paper, we described the case of the migrated biliary stent with prolonged abdominal pain, which was removed successfully by using double-balloon. Conclusion: In the case of patient with prolonged abdominal pain and previous history of biliary stent placement, migration of stent should be considered as differential diagnosis and Double-Balloon Enteroscopy can be a safe approach in those cases.[GMJ.2020;9:e1809]